PEMASARAN BUAH NENAS (KAJIAN STRUKTUR, PERILAKU, DAN PENAMPILAN PASAR) DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Sandro Chrystop Sinaga; Novia Dewi (Universitas Lancang Kuning, 2016)
This study aims to identify marketing channels and market structure pineapple, pineappleanalyzing market behavior and analyzing the performance of pineapple fruit market in thevillage of Kualu Nenas. The data collection method is a survey method. Determination bypurposive sampling of respondents and the formula slovin on pineapple growers as much as33 farmers. Determination of the number of traders, wholesalers and agents agroindustrialdetermined by census where traders, wholesalers and agents agroindustrial taken based on theaccumulation of 33 farmers who sell pineapples to traffickers and agro industry in the villageKualu Nenas, there are 8 traders , 6 wholesalers, and 8 players in the industry. Descriptiveanalysis of data on the market structure and concentration ratio harfindahl index (HI), for thebehavior of markets analyzed by correlation and elasticity of the transmission, and theappearance of markets analyzed by the equation margin trading system. The results showedthe market structure market share, concentration ratios, and HI traders at 0.5469, 54.69%, and0.2990, market share, concentration ratios, and HI wholesalers at 0.6878, 68.78%, and0.4730, and market share, concentration ratios and HI agro-industry amounted to 0.5145,51.45%, and 0.2647 of its market structure among the three is oligopsony. Market behaviorindicates correlation values 0523 and 0515 transmission elasticity analysis. Appearancemarket views on marketing margin is relatively large and is dominated by the great resultsand uneven. Apart from it can be seen also from the uneven distribution margin, the shareprice received by farmers is still relatively low and the ratio of benefits and costs to farmers isstill low. In addition, the bargaining power of farmers is weak because prices are determinedunilaterally by traders, especially on the channel I and channel II while the third channel isrelatively better because of the level of efficiency is lower